Customer experience in immersive virtual reality retail : exploring behaviors, emotions, and touchpoints across the shopping journey : a thesis with publications presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Information Technology, School of Mathematical and Computational Sciences, Massey University, Albany, Auckland, New Zealand - Erensoy, Aysu (Massey University, 2025)
Immersive Virtual Reality (iVR) is transforming the retail landscape by merging sensory engagement with the personalization and convenience of digital platforms. As part of the rapidly evolving metaverse, iVR has the potential to redefine customer experience (CX) and create immersive, multisensory shopping environments. However, understanding how iVR shapes customer behaviors, emotions, and interactions across the shopping journey remains limited. These gaps hinder businesses from fully optimizing CX in this emerging domain. This research aims to address these challenges by exploring the influence of iVR retail touchpoints on CX and developing frameworks to advance theoretical and practical knowledge in iVR retail. This study employed a human-centered design methodology, integrating systematic literature reviews, semi-structured interviews with VR design experts, and iVR experiments with end-users. The literature review established a theoretical foundation, identifying challenges and opportunities in iVR retail. Semi-structured interviews with experts explored critical touchpoints, emotions, behaviors, and the design processes underlying iVR environments. Complementing these, VR experiments, card-sorting activities, and end-user interviews captured the behaviors and emotions of participants across the pre-purchase, purchase, and post-purchase stages of the shopping journey. This study offers significant theoretical advancements by extending the Stimulus-Organism-Response (S-O-R) model to better capture the complexities of CX in immersive virtual environments. It provides a nuanced understanding of how sensory stimuli influence emotional responses and consumer behaviors, particularly within iVR retail contexts. This extension enables a more comprehensive analysis of the relationships between touchpoints, emotions, and shopping processes. Additionally, the study adapts the Double Diamond framework, tailoring it to meet the unique demands of iVR design. This refined framework supports designers in addressing the iterative nature of immersive retail experiences across discovery, definition, development, and delivery phases. Additionally, the key outcome of this research is developing a CX framework that detailed the iVR customer journey, illustrating how user interactions, emotional responses, and behaviors evolve across the pre-purchase, purchase, and post purchase stages. These findings not only highlight the underlying mechanics of creating positive CX in iVR environments but also identify the drivers of emotional connection and satisfaction, laying the groundwork for further exploration and application in this transformative retail medium. This research contributes to both theoretical and practical understanding of iVR retail environments. Theoretically, it advances models such as the S-O-R model and refines the Double Diamond framework, aligning them with the complexities of immersive technologies and offering tools for analyzing how iVR reshapes CX. Practically, the study provides actionable design guidelines to address key challenges in iVR retail, including improving usability with intuitive interfaces, enhancing accessibility through features like voice navigation, and fostering emotional engagement via sensory-rich experiences. These guidelines support the creation of inclusive, engaging, and effective iVR shopping environments that serve as a roadmap for future studies for exploring and validating emergent technological innovations in iVR retail.
Keywords: customer experience, consumer behavior, virtual reality, human-centred design, human-computer interaction; Marketing; Technological innovations; Interactive marketing; Shared virtual environments; Electronic commerce; Psychological aspects; Consumer behavior; 460708 Virtual and mixed reality; 350602 Consumer-oriented product or service development